Hubungan Pengetahuan, Pendidikan dan Usia Ibu dengan Pemberian Imunisasi Dasar Lengkap pada Bayi Umur 0-12 Bulan di Praktik Mandiri Bidan (PMB) Hj. Rusmala Aini SST - Rahmah, Rahmah; Rian, Aristy; Putri, Avinda; Haryanti, Dwi; Yanti, Maulida (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the relationship between knowledge, education and maternal age with the provision of complete basic immunization to babies aged 0-12 months at the Independent Midwife Practice (PMB) Hj. Rusmala Aini. This census research used quantitative methods with univariate and bivariate analysis. The participants in this research were mothers who visited PMB Hj Rusmala Aini, which included 40 babies. The results of this study reveal that there is a relationship between the level of education and the mother's age and the provision of complete basic immunization to babies aged 0-12 months at the Independent Midwife Practice (PMB) Hj. Rusmala Aini, but there is no relationship between mothers' knowledge of providing complete basic immunization to babies aged 0-12 months.